Synesthesia in Graphic Notation: Visual Languages for the Representation of Sound - Buj Corral, Marina (2018)
To represent the different sound phenomena, graphic notation— musical writing originated in the middle of the last century— uses a great variety of visual language elements. In this type of notation, the score acts not only as a record and motor of the musical experimentation carried out by the avant-garde composers, but also as a territory of trials and tests with the different visual languages. This article delves into the knowledge of the different visual languages used in the graphic notation with the purpose of understanding how the musical concept of each work and composer is related to the visual language chosen for its graphic representation. For this, an interdisciplinary study of certain representative works of graphic notation made from the mid-20th century to the present day has been carried out, selecting the visual languages of comics, collage, sculpture, video and film, photography and drawing. The research evidences the synesthetic nature of the graphic notation and highlights the creative nature of this form of musical writing, as a generator of new sound and artistic processes, as well as interpretative suggestions and resources. This article focuses on the study of graphic notation as a synesthetic, musical and plastic phenomenon. Additionally, it adopts as starting point the own visual language of each score in order to, based on it, understand how image and sound create a dialogue in each case, how musical thinking materializes in a work that is also plastic, and vice versa, how a plastic work generates new sound processes.